Increased expression of TLR7 and TLR9 in alopecia areata. Issue 3 (14th October 2019) - Kang, Hoon; Wu, Wen‐Yu; Yu, Mei; Shapiro, Jerry; McElwee, Kevin J.
Abstract: Alopecia areata (AA) is thought to be an autoimmune process. In other autoimmune diseases, the innate immune system and Toll‐like receptors (TLRs) can play a significant role. Expression of TLR7, TLR9 and associated inducible genes was evaluated by quantitative PCR in peripheral blood mononuclear cells (PBMCs) from 10 healthy individuals and 19 AA patients, categorized according to disease duration, activity and hair loss extent. Microdissected scalp biopsies from five patients and four controls were also assessed by quantitative PCR and immunohistology. TLR9 was significantly upregulated 2.37 fold in AA PBMCs. Notably, TLR9 was most significantly upregulated in patients with active AA, as shown by a positive hair pull test, compared to stable AA patients. In hair follicle bulbs from AA patients, IFNG and TLR7 exhibited statistically significant 3.85 and 2.70 fold increases in mRNA, respectively. Immunohistology revealed TLR7 present in lesional follicles, while TLR9 positive cells were primarily observed peri‐bulbar to AA affected hair follicles. The increased expression of TLR7 and TLR9 suggest components of the innate immune system may be active in AA pathogenesis.